SAT0245 Elevated serum levels of sclerostin and periostin protect against syndesmophyte formation in patients with ankylosing spondylitis and high activity of systemic inflammation. (23rd January 2014) - Poddubnyy, D.; Conrad, K.; Ruiz-Heiland, G.; Syrbe, U.; Haibel, H.; Appel, H.; Rudwaleit, M.; Schett, G.; Sieper, J.
Abstract : Background: High and persistent activity of systemic inflammation (e.g., elevated serum level of C-reactive protein (CRP)) was found recently to be an independent predictor of radiographic spinal progression in patients with ankylosing spondylitis (AS). At the same time several biomarkers were found to be protective regarding progression of spinal damage in AS: sclerostin, Dickkopf 1 (DKK1), and periostin. However, due to lack of correlation between serum levels of protective and predictive biomarkers, their relationship remains unclear until now. Objectives: To investigate the association of protective biomarkers with radiographic spinal progression (new syndesmophytes formation or growth of the existing syndesmophytes) in patients with AS in relation to activity of systemic inflammation. Methods: Altogether 104 patients with AS from the German Spondyloarthritis Inception Cohort (GESPIC) were included in the analysis. Radiographs of the lumbar and cervical spine performed at baseline and after 2 years of follow-up were centrally collected, digitized, and subsequently scored independently by two trained readers. Serum levels of C-reactive protein (CRP) were measured at baseline and every 6 months thereafter, a time-averaged value was calculated. Serum levels of sclerostin and DKK1 were measured at baseline, after 1 and 2 year of follow-up (time-averaged values were also calculated), periostin serum level was measured at baseline samples. Threshold for elevated/non-elevated levels were chosen on the basis of median values in the whole group. Results: In total, 33 patients (31.7%) demonstrated new syndesmophytes formation or progression of existing syndesmophytes over two years, which was clearly associated with elevated (>6 mg/l) time-averaged CRP: 47.1% (n=24) of the patients with elevated CRP vs. 17.0% (n=9) of the patients with normal CRP demonstrated such a progression, odds ratio (OR) =4.4 (95%CI 1.8-10.7), p=0.001. However, 52.9% (n=27) of the patients with elevated CRP were free of radiographic progression in the spine. In the group of patients with elevated CRP, 35.7% of the patients with high time-averaged sclerostin serum level (>0.4 ng/ml, n=14) and 75% of the patients with low level (≤0.4 ng/ml, n=16) demonstrated radiographic progression (OR=0.19, 95%CI 0.04 to 0.89, p=0.036). Similarly, 37.5% of the patients with high baseline periostin level (>37 ng/ml, n=16) and 71% with low level (≤37 ng/ml, n=21) demonstrated such a progression (OR=0.24, 95%CI 0.06 to 0.96, p=0.044). The same trend, although statistically non-significant, was found for time-averaged DKK1: 44.4% of the patients with high (>4.8 ng/ml, n=18) and 66.7% with low (≤4.8 ng/ml, n=15) serum level demonstrated progression, OR=0.40, 95%CI 0.10 to 1.66. Importantly, no significant association between analysed biomarkers and radiographic progression was found in patients with normal CRP. Conclusions: Elevated levels of sclerostin and periostin, and, to a lesser extent, Dickkopf 1 are protective regarding syndesmophyte development/progression in AS patients in the presence of elevated CRP. This might explain lack of syndesmophytes in a part of patients with AS despite persisting activity of systemic inflammation. Disclosure of Interest: None Declared